Children’s Education Through The Method Of Setting A Good Example: A Thematic Study Of The Qur’an, Surah Al-Ahzab, Verse 21 - Mudhofar (Journal Innovative Practices in Education (JIPE), 2025)
Children’s education is a fundamental aspect of the formation of human character and personality. One highly effective educational method in Islam is the method of setting a good example (uswah hasanah). This article aims to examine the concept of children’s education through the method of setting a good example based on a thematic study of Surah Al-Ahzab, verse 21, of the Qur’an. This research employs a qualitative method using a library research approach, which involves gathering data from the Qur’an, hadith, exegetical works, and relevant literature on Islamic education. The research findings indicate that Surah Al-Ahzab, verse 21, affirms the Prophet Muhammad (peace be upon him) as the best role model for humanity. The concept of exemplary behaviour in this verse has significant implications for children’s education, particularly in the development of character, morals, spirituality and social skills. Parents and educators are required to be role models capable of setting a tangible example through their daily behaviour. The role-modelling approach has proven to be more effective than purely instructional methods, as children tend to learn through imitating their surroundings. Therefore, child education based on role modelling is a relevant strategy for shaping a generation with Islamic character.